Promote educational success: what is the contribution of Learning Analytics to educational research? - Pandolfi, Luisa (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
The notion of educational success is broad and multidimensional and refers to the full and authentic personal and social realization of students. The European Council in 2018 suggest the importance of providing support to all students for the development of their skills and resources, including those in disadvantaged conditions or with specific needs. But in Europe and, specifically, in Italy can we talk about educational success or failure? The rates of early school leaving are still very high; the scientific literature focuses in adopting systemic models and interpretations of the phenomenon. The importance of having data and observable and measurable indicators emerges and, at the same time, to bring out the perception and the meaning attributed by the protagonists to their experience, paying attention to the contextual dimensions. The paper explores some points of intersection between the strategies of intervention and contrast to the early school leaving, the educational research and the current challenges of Learning Analytics, in order to outline possible directions of analysis and empirical investigation to improve the learning processes and teaching, educational practices and contexts.